Spatial scale effect on seasonal streamflows in permafrost catchments on the Qinghai-Tibet Plateau - Wang, Genxu; Liu, Guangsheng; Liu, Lin'an (Hydrological Processes, 2012)
The scale issue is of central concern in hydrological processes to understand the potential upscaling or downscaling methodologies, and to develop models for scaling the dominant processes at different scales and in different environments. In this study, a typical permafrost watershed in the Qinghai-Tibet Plateau was selected. Its hydrological processes were monitored for 4 years from 2004 to 2008, measuring the effects of freezing and thawing depth of active soil layers on runoff processes. To identify the nature and cause of variation in the runoff response in different size catchments, catchments ranging from 1.07 to 112 km2 were identified in the watershed. The results indicated that the variation of runoff coefficients showed a V shape with increasing catchment size during the spring and autumn seasons, when the active soil was subjected to thawing or freezing processes. A two-stage method was proposed to create runoff scaling models to indicate the effects of scale on runoff processes. In summer, the scaling transition model followed an exponential function for mean daily discharge, whereas the scaling model for flood flow exhibited a linear function. In autumn, the runoff process transition across multiple scales followed an exponential function with air temperature as the driving factor. These scaling models demonstrate relatively high simulation efficiency and precision, and provide a practical way for upscaling or downscaling runoff processes in a medium-size permafrost watershed. For permafrost catchments of this scale, the results show that the synergistic effect of scale and vegetation cover is an important driving factor in the runoff response. Copyright (C) 2011 John Wiley & Sons, Ltd.